Traditional Instruments for Reducing Human Risk in The Banking Sector - Jan KOLEŚNIK (Communications of International Proceedings, 2022)
The aim of this article is to perform a critical evaluation of the theory and practice of human risk management in the contemporary banking system with special focus on post-crisis regulations on capital requirements and banking executives’ remuneration policies. The analysis has shown that traditional instruments used to reduce human risk in the banking sector, i.e. regulations on remuneration rules – although perfectly reasonable – cannot be treated as tools which can effectively solve the problem of human risk.
Keywords: banks; human risk; operational risk